2014
DOI: 10.1002/hec.3084
|View full text |Cite
|
Sign up to set email alerts
|

How Do Smokers Respond to Cigarette Taxes? Evidence from China's Cigarette Industry

Abstract: This paper examines how Chinese smokers respond to tax-driven cigarette price increases by estimating a discrete choice model of demand for differentiated products, using annual nationwide brand-level cigarette sales data in China from 2005 to 2010. We allow for substitution between different cigarette brands and also incorporate key features of rational addiction theory into the model. Results show that the average own-price elasticity of demand for cigarettes at the brand level is -0.807, and the overall pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 49 publications
(87 reference statements)
2
13
0
4
Order By: Relevance
“…For example, recent studies have found that the price elasticity of demand for cigarettes in China is around −0.5 27 , 28 . This is similar to estimates from other developing countries, meaning that a 10% increase in the price of cigarettes will reduce cigarette consumption by 5% 29 .…”
Section: Early Outcome Assessmentsupporting
confidence: 61%
“…For example, recent studies have found that the price elasticity of demand for cigarettes in China is around −0.5 27 , 28 . This is similar to estimates from other developing countries, meaning that a 10% increase in the price of cigarettes will reduce cigarette consumption by 5% 29 .…”
Section: Early Outcome Assessmentsupporting
confidence: 61%
“…This contrast supports the view that price elasticity may be country specific e.g., due to the market structure, patterns of consumption, and government role and associated policies [12][13][14][15][16]. For instance, some authors of studies in developing countries, Kenkel et al [17], Lance et al [18], and Liu et al [10] find weak evidence of tax or price effect on tobacco demand. In addition to these studies Ross et al [19] found that this trend might derive from the wide range of cigarette prices available on the market, high social acceptability of smoking, and stockpiling effects.…”
Section: Introductionsupporting
confidence: 52%
“…Furthermore, the lack of data availability on the age and gender of tobacco users, due to lack of individual data, does not allow us to estimate price elasticity by age or gender. Elasticity coefficients differ in terms of age, gender and incomes, time observed, and brands [10,38]. The youth in several low-income countries is found to be more responsive to cigarette price changes than other age cohorts [39,40].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations